Destabilization of Energy Regimes and Liminal Transition Through Collective Action in Chile - Baigorrotegui-Baigorrotegui, G (Elsevier Ltd, 2019)
The transition of energy policy towards fairer and more sustainable paths has centered on the dynamics of destabilization processes in energy regimes. Much has been written about the complex nature of transitions in the sector in 30-40 year cycles, but less work has been done on disruptive destabilizations over shorter periods, especially focussing on how they are produced and intensified. Through a qualitative examination of two failed large electricity projects in Chile, we investigate how collective action can influence the destabilization of an electricity regime through interaction between the day-to-day dramaturgical actions of the so-called communitas and media actors. Both projects, a hydro-dam plant and a coal-fired power plant (CFPP), offer unprecedented examples of how two transnational energy consortium projects were halted, mainly by effective collective actions that occurred within Chile s neoliberal landscape to combat these energy initiatives. We propose an interpretation of the dynamics of regime destabilization from a dramaturgical-materialistic perspective that allows a new conception of how energy transitions occur. Through this perspective, we shed light on new entanglements, actors and new questions that arise regarding how transitions become real. We propose the mechanisms of i) pressure, ii) obstruction and iii) public overflow to trace the activities that bring a liminal energy transition into view. © 2019 Elsevier Ltd